Pollination biology and breeding system of syntopic Adenocalymma nodosum and A. peregrinum (Bignonieae, Bignoniaceae) in the Brazilian savanna - Sampaio, Diana S.; Mendes-Rodrigues, Clesnan; Engel, Thaissa B. J.; Rezende, Tiago M.; Bittencourt-, Nelson S. [UNESP]; Oliveira, Paulo Eugenio (Elsevier B.V., 2016)
The tropical Bignoniaceae is mostly late-acting self-incompatible (LSI) and depends on a guild of medium to large sized bees for their pollination. Adenocalymma nodosum and A. peregrinum are syntopic shrubs in savanna areas with similar flowers and flowering overlap. In this sense, the aims of the present study were to analyse the pollination biology and breeding systems of these species, and to check for bilateral compatibility which could hinder reproductive isolation and species boundaries. Flower features such as yellow corolla, sweet scent and diurnal one-day anthesis were similar between species. However, they differed in nectar production patterns, which showed higher volume in A. nodosum and was irregular in A. peregrinum. The main pollinators for both species were medium to large Centridini bees. Many nectar and pollen robbers may disturb effective pollination and help to explain the low natural fruit-set. The species were self-sterile but pollen tube growth down to the ovules and differential ovary development indicated LSI, as in most Bignoniaceae studied to date, which reinforce the idea of family, clustering for this self-incompatibility system. Fruit-set from interspecific hand pollinations was similar to those of intraspecific cross-pollinations, with high seed viability (88%) and seedling development. Similar floral biology and guild of pollinators, and bilateral inter-compatibility indicate that natural hybridization is possible among these species. (C) 2016 Elsevier GmbH. All rights reserved.
Keywords: Cerrado; Interspecific compatibility; Late-acting self-incompatibility; Synchronopatry